Can Speaker Gaze Modulate Syntactic Structuring and Thematic Role Assignment during Spoken Sentence Comprehension? - Knoeferle, Pia; Kreysa, Helene (Frontiers in Psychology, 2012)
During comprehension, a listener can rapidly follow a frontally-seated speaker's gaze to an object before its mention, a behavior which can shorten latencies in speeded sentence verification. However, the robustness of gaze-following, its interaction with core comprehension processes such as syntactic structuring, and the persistence of its effects are unclear. In two ``visual-world'' eye-tracking experiments participants watched a video of a speaker, seated at an angle, describing transitive (non-depicted) actions between two of three Second Life characters on a computer screen. Sentences were in German and had either subject(NP1)-verb-object(NP2) or object(NP1)-verb-subject(NP2) structure; the speaker either shifted gaze to the NP2 character or was obscured. Several seconds later, participants verified either the sentence referents or their role relations. When participants had seen the speaker's gaze shift, they anticipated the NP2 character before its mention and earlier than when the speaker was obscured. This effect was more pronounced for SVO than OVS sentences in both tasks. Interactions of speaker gaze and sentence structure were more pervasive in role-relations verification: Participants verified the role relations faster for SVO than OVS sentences, and faster when they had seen the speaker shift gaze than when the speaker was obscured. When sentence and template role relations matched, gaze-following even eliminated the SVO-OVS response time differences. Thus, gaze-following is robust even when the speaker is seated at an angle to the listener; it varies depending on the syntactic structure and thematic role relations conveyed by a sentence; and its effects can extend to delayed post-sentence comprehension processes. These results suggest that speaker gaze effects contribute pervasively to visual attention and comprehension processes and should thus be accommodated by accounts of situated language comprehension.